PDF/A-3 solution for digital calibration certificates - Gregor Boschung (Measurement: Sensors, 2021)
The digitalization of metrology poses a challenge to all members of the metrology community. We propose an approach for digital calibration certificates (DCCs) based on a PDF/A-3 solution that could be a stepping-stone towards the digitalization of metrological services. We present multiple applications of this approach by fulfilling discussed minimum requirements and satisfying needs from both customers and laboratories.